CLASSIFICATION OF HEAVY METALS IN MEAT AND DAIRY PRODUCTS BASED ON THE DEFINITION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this state, meat and dairy products and ix the content of heavy metal salts are investigated and analyzed. The influence of heavy metal soles on human health has been studied. And also the content of heavy metals in meat and milk samples corresponded to state standards: 3,8% in cow milk, 4,5% in camel milk, 1,8% in birch milk and 6,7% in sheep milk. Modern organoleptic and physicochemical methods for determining the quality of these goods have been developed and introduced into customs practice.